(untitled) (Conferencea, 2022)
Ground with several types of building materials are used in production of the roller. Depending on the degree of crushing of materials, the output device in the hole: a) large b-crushing Secondary crushing v)finely crushing. Depending on the expenses to the advantage of: a) Stasionar b) xarakatlanuvchi. Grate depending on the number of the working rollers: a)with a roller b)a roller with two c)three rollers g) with four roller [1-8].